Frozen Forest in the Chrysler Pavilion
Men from left to right: W.P. Chrysler Jr. O.R. Skelton, Executive Engineer J.E. Fields, Vice President Waddill Catchings Byron C. Foy, Vice President Harry Bronner F.M. Zeder, Vice Chairman of the Board Harold E. Talbott K.T. Keller, President and Raymond Loewy, designer of the pavilion. Chrysler, Catchings, Bronner, and Talbott were directors of the Chrysler Corp.